2020
DOI: 10.3390/genes11080897
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Pathway Genetic Variation and Type 1 Diabetes: A Case–Control Association Study

Abstract: Vitamin D has immunomodulatory effects, and its deficiency has been implicated in the autoimmune process of type 1 diabetes. Serum vitamin D levels are influenced by variants in genes involved in the synthesis, transport, hydroxylation and degradation of vitamin D. The aim of this study was to assess if single nucleotide polymorphisms (SNPs) at the DHCR7 (rs12785878), GC (rs2282679), CYP2R1 (rs2060793) and CYP24A1 (rs6013897) loci are associated with type 1 diabetes in the Portuguese population. Genotype and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…CYP2R1 rs12794714 and rs10766196 polymorphisms were associated with a high risk of T1DM, and polymorphisms in vitamin D metabolism could lead to susceptibility to T1DM in Korean children [60]. Another similar study showed a cumulative effect of SNPs at the CYP2R1 (rs2060793), DHCR7 (rs12785878), GC (rs2282679), and CYP24A1 (rs6013897) loci on the susceptibility to type 1 diabetes [61]. Tangjittipokin et al [62] found SNPs and T1DM in CYP2R1 (rs10741657) (GA, OR: 1.83, 95% CI: 1.01-3.31; p = 0:04).…”
Section: Polymorphisms Of Vitamin D Metabolismmentioning
confidence: 84%
“…CYP2R1 rs12794714 and rs10766196 polymorphisms were associated with a high risk of T1DM, and polymorphisms in vitamin D metabolism could lead to susceptibility to T1DM in Korean children [60]. Another similar study showed a cumulative effect of SNPs at the CYP2R1 (rs2060793), DHCR7 (rs12785878), GC (rs2282679), and CYP24A1 (rs6013897) loci on the susceptibility to type 1 diabetes [61]. Tangjittipokin et al [62] found SNPs and T1DM in CYP2R1 (rs10741657) (GA, OR: 1.83, 95% CI: 1.01-3.31; p = 0:04).…”
Section: Polymorphisms Of Vitamin D Metabolismmentioning
confidence: 84%
“…On the other hand, one mendelian randomization study including single nucleotide polymorphisms (SNPs) that are associated with 25(OH)D levels included in a large vitamin D genome-wide association study (GWAS) on more than 400,000 Europeans demonstrated that 25(OH)D levels were unlikely to present an impact on the risk of developing T1D [ 214 , 233 ]. Another case-control study did not register a significant association of each SNP (DHCR7, GC, CYP2R1 and CYP24A1 genes) with T1D but demonstrated a combined effect of multiple risk alleles [ 214 , 234 ].…”
Section: Vitamin D and Immune-related And Autoimmune Diseasesmentioning
confidence: 99%
“…In patients, the TT genotype of the rs2228570 variant showed higher levels of 25(OH)D compared to CC + TC in the same polymorphism. Type 1 Diabetes Almeida, J 2020 [ 213 ] Portugal Case-Control 350/490 29 ± 11.1/32,2 ± 11.2 PCR-RFLP and TaqMan Genotyping Assay Sex and age DHCR7, GC, CYP2R1 and CYP24A1 DHCR7 (rs12785878), GC (rs2282679), CYP2R1 (rs2060793) and CYP24A1 (rs6013897) The frequency of each SNP alone was not significantly different between patients and controls. However, was observed a cumulative effect of minor alleles of SNPs at the DHCR7, GC, CYP2R1 and CYP24A1 loci on the susceptibility to type 1 diabetes.…”
Section: Resultsmentioning
confidence: 99%